Uwarunkowania instytucjonalne niemieckiego rynku pracy wobec swiatowego kryzysu gospodarczego 2008-2009 - Michal Moszynski (Institute of Economic Research (IER), 2015)
– The unemployment rate in Germany after reaching a peak of 12.1% in 2005 began to decline steadily, and the improvement of the situation on the labour market followed even in the face of the global economic crisis after 2007. These positive trends, especially in comparison with other EU countries, draw attention and are discussed in the literature. Reference is made to the exceptionally favourable macroeconomic configuration for the German economy: low interest rates (since autumn 2008), low oil prices and the weak euro (since mid-2014). Secondly, an active employment and the labour market policy is boasted in the face of crisis. Finally, the institutional aspects of the German labour market are emphasized: long-term effects of labour market reforms as part of the Hartz package of 2003-2005 and the specificity of the German model of industrial relations as an effective constellation of three key actors in the labour market: trade unions, employers' organizations and works councils. The objective of this study is an attempt to clarify the institutional conditions of the functioning of the labour market in Germany that are relevant to the response to the crisis. Accordingly, the buffers are examined to mitigate shocks with particular emphasis on instruments of internal flexibility, social partners behaviour and institutional connections of labour markets with other domains of economic order on the example of dual education system.
Keywords: E24; H12; J52; A11; A14; B16; 330; crisis; Germany; labour market institutions; employment; unemployment